Large reductions in cesarean delivery rates in China: a qualitative study on delivery decision-making in the era of the two-child policy - Eileen Wang; Therese Hesketh (BMC, 2017)
Abstract Background In 2010, China's cesarean delivery (CD) rates increased to one of the highest in the world, a significant proportion of which were without medical indication. However, recent studies have indicated some declines, coinciding with national and local efforts to promote vaginal birth, as well as the relaxation of the one-child policy. Considering these trends, we aimed to qualitatively explore attitudes towards childbirth and experiences of delivery decision-making among women and physicians. Methods Semi-structured interviews were conducted with 45 postpartum women and 7 healthcare providers at one county-level and one provincial-level maternity hospital in Zhejiang Province. We also collected routine data from 2007 to 2016 and observed doctor-patient interactions and hospital facilities as context for the interviews. Interviews were recorded, translated and transcribed into English, and then analyzed using a framework approach. Results From 2007 to 2016, cesarean delivery rates at the county-level and provincial-level hospital decreased from 46% to 32% and 68% to 44%, respectively. For low-risk women, vaginal birth was the primary choice of delivery method, encouraged by doctors and nurse-midwives. Elective CD was not as widely accepted, in contrast to previous years. Women were aware of and took into consideration the consequences of CD for future pregnancies. Among those who delivered vaginally, women viewed the existing pain relief methods, epidurals and transcutaneous electrical nerve stimulation, with caution or uncertainty. Even when requested, epidurals were only given under certain circumstances. For multiparas with previous CD, repeat CD remains the norm. Both women and professionals were cautious about vaginal birth after cesarean delivery (VBAC) given the associated risks. Conclusion In China, changes in family planning policy and efforts to promote vaginal birth have greatly changed the culture of delivery decision-making, leading to decreased CD rates. This demonstrates the powerful role social factors and public policy can play, and provides a model for other countries with high CD rates. Further research should explore changes in other reproductive decisions during this new multiparous era, particularly across provinces.